Co-movement between the US and the securitised real estate markets of the Asian-Pacific economies. Issue 1 (2nd January 2019) - Liow, Kim Hiang; Zhou, Xiaoxia; Li, Qiang; Huang, Yuting
ABSTRACT: The novelty of this study is the use of continuous wavelet transform analysis of wavelet coherence, as well as its partial and multiple forms, to revisit the co-movements of Asian-Pacific public real estate markets among themselves and with the US, for a time span which covers the 12 January 1995–23 June 2016 period. Earlier research does not have satisfactory results because traditional methods average different relationships in time domain only. From the wavelet analysis, investors can extract the time-scale that most interests them. We find that the co-movement relationship across the real estate markets increases during the two major crisis period, as well as becomes stronger as the scale increases. Hong Kong and Singapore have the strongest time-scale co-movement relationship. Finally, the influence of domestic macroeconomic factors on real estate return co-movement appears to be greater at the long-term horizons than at the short-term horizons.